Influence of Community‐Based Dental Education on Practice Choice: Preliminary Data from East Carolina University - Gordon, Sharon; Warren, Abigail C.; Wright, Wanda G. (My University, 2019)
Maldistribution of the dental workforce contributes to poor access to oral health care. Community‐based dental education (CBDE) may help to address this problem by using experiential learning to encourage new dentists to practice in underserved areas. The East Carolina University School of Dental Medicine (East Carolina University SoDM) employs a multifaceted strategy, including CBDE, to increase the number of dentists practicing in underserved areas of North Carolina. The aim of this study was to assess the influence of CBDE and other factors on practice choice among East Carolina University SoDM graduates. This cross‐sectional study assessed practice intentions before and after a senior‐year CBDE experience. Data were obtained for students in three graduating years from written student reflections and self‐reported practice plans solicited at graduation. Of the total 156 students between 2015 and 2017 (52 each year), all students participated in at least one component of this evaluation: all students (100%) completed required student reflections, and 148 (95%) provided pre‐graduation practice plans. Data were also obtained on alumni practice characteristics via a survey of recent graduates; 72 alumni (46% response rate) participated in the alumni survey. The assessments found positive attitudes towards the CBDE program before and after participation, although areas for improvement relating to business management and financial viability were reported. The majority of alumni respondents (67%) remained in the state to practice after graduation, with half reporting practicing in rural areas. For most alumni respondents (>75%), debt, salary, benefits, type of patient population, and desire to own/run a business were important factors other than the CBDE program influencing their practice choice. Nearly half of them (45.8%) rated desire to work in a public health setting as an important factor. This study provides preliminary evidence of the effectiveness of this educational model in retaining new dentists within the state to address the critical shortage of dentists in North Carolina.